More Markets, More Justice - Hadfield, Gillian K. (Daedalus, 2019)
People lack access to justice because the law is complex and expensive to use. Basic mechanisms of market competition can reduce both the complexity and the cost of law while securing law's principal function in society, which is to coordinate a community around a shared understanding of what is and what is not allowed. Creating markets for rules will make for better law and better legal systems by allowing people and organizations to select the rules and dispute-resolution processes that are best for them in a market in which providers of regulation compete on terms of cost and quality. Legal rules require special protection to make sure they deliver a more just, equitable world for all; this protection can be provided through a “superregulator,” which licenses providers of law and legal services to sell their services in competitive markets.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2Mi9kYWVkX2FfMDA1MzM